Tell the story of all this: the place of the fire in the hermeneutics of Derrida and Agamben. Issue 1 (2nd January 2021) - Willemse, Arthur
ABSTRACT: This essay examines the question of place as a pivotal moment for contemporary hermeneutics. Taking my cue from Ahmet Altan's recent formulation of the writer's paradox, and by visiting Giorgio Agamben's recent citation of a legendary lineage of Hasidic rabbis, I describe a hermeneutical oscillation between two poles, the fire and the tale, to bring out the difficulty that narrative has when 'place' is its object. Accordingly, I set up the very different comportments that Jacques Derrida and Agamben display towards hermeneutics as well as with a view to the history of thought. From this exposé, I will explain the two philosophers' main topographical indicators, trace and archē, and conclude by bringing out how the tradition of thought is warped by its fusion to the rabbinical line that goes back to the fire.